The Effect of Programmatic Advertising, Interactive Content andPromotion Strategy towards Brand Management in the Jordanian Context - Loma shafiq MOH'D Naji, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of this research was to analyze the influence of programmatic advertising, interactive content, and promotion strategy on brand management. A specific aim guided the research; to evaluate digital marketing new tools in Jordan that can affect brand management. Furthermore, questionnaires were given based on a simple sampling technique and acquired in the Jordanian market. 316 questionnaires were distributed, and 280 available samples were gathered, resulting in a 88% response rate for all those selected to participate. Descriptive analysis, reliability test, correlation test, was used in this research. Moreover, this study’s results demonstrated a robust positive relationship between programmatic advertising, interactive content, and promotion strategy and brand management. However, Jordanian students used platforms that use programmatic advertising and interactive content, and they think, based on the analysis of their perception, those tools affect brand management. Finally, the results of this study suggest that firms should adopt those tools with suitable promotion strategies to enhance brand management to leverage the digital world and technology, increase brand awareness through digital platforms used programmatic advertising and interactive content to continue competing in today’s commercial environment.